Incidence of dengue in a rural hospital, Chinakakani, Andhra Pradesh, South India and comparison of two commercially available enzyme linked immunosorbent assays with immunochromatographic rapid test - Prudhivi, Sumana; Yenigalla, Bindu Madhav; Myneni, Ramesh Babu (International Journal of Research in Medical Sciences, 2017)
Background: Dengue is one of the most serious mosquito borne arboviral infections affecting tropical and subtropical countries in the world. Since there is no immune prophylactic or specific anti-viral therapy available, timely and rapid diagnosis plays a vital role in patients management and implementation of control measures. This work has been taken up 1. To study the incidence of dengue cases in our rural hospital, Chinakakani, South India. 2. To compare the performances of Pan Bio capture ELISA [PanBio], J Mitra Microlisa [J Mitra] and SD BIO dengue duo rapid test [SD RT]. Methods: A total of 1180 serum samples from clinically suspected dengue cases were collected over a period of seven months. All the samples were subjected to NS1 antigen and IgM antibody Pan Bio ELISA. The same were tested for J Mitra Microlisa and SDRT and were compared with Pan Bio. Measure of discrimination i.e. sensitivity and specificity was calculated for each observed test value and an receiver operating characteristic [ROC] curve was constructed to compare the area under curve’s [AUC] of different test kits thereby identifying the test with the best discriminative value. Results: Out of 1180 samples tested, Pan Bio has shown an incidence rate of 284 [24.06%] (NS1 156+IgM 128), J Mitra 280 [23.72%] (NS1 156 + IgM 124) and SDRT 292 [24.74%] (NS1 156+IgM 136). As far as NS1 is concerned the same 156 samples were positive in all the three tests giving the sensitivity, specificity, positive and negative predictive values 100%. Remaining 1024 samples were negative for NS1. But this was not the case with IgM. AUC of IgM Pan Bio is 0.944 with sensitivity 90.32% and specificity 98.48%. AUC of IgM J Mitra is 0.932 with sensitivity 81.62% and specificity 98.75%. AUC of IgM SD RT is 0.992 with sensitivity 99.2% and specificity 99.1%. ‘Z’ test revealed that there is statistically significant difference between AUC’s of SD RT when compared to Pan Bio (p value: 0.05) and J Mitra (p value 0.0001) The p values explain that SD RT is superior to Pan Bio and J Mitra in classifying between diseased and non-diseased. Conclusion: High incidence rate was noticed in our region during monsoon and post-monsoon season which calls for timely preventive and control measures. SDRT is a valuable screening test in laboratories with minimal resources.